Studies on in-vitro maturation, fertilization and cleavage rate of prepubertal and pubertal goat oocytes - SINGH, K P; SAXENA, ATUL; KHARCHE, S D; SINGH, PRANEETA (The Indian Journal of Animal Sciences, 2011)
The experiment was carried out with the aim to study the maturation and cleavage rate of prepubertal and pubertal goat oocytes, matured in-vitro with maturation media TCM–199 containing either 20% estrous goat serum (EGS), 20% new calf serum (NCS), 10% new calf serum (NCS) + hormone (FSH + LH + E2) or 20% caprine follicular fluid (CFF). Maturation was assessed 27 h after incubation of oocytes in culture (in a CO2 incubator in humidified air at 38.5±1°C with 5% CO2). On morphological basis, the maturation rate (%) of oocytes for prepubertal and pubertal animals was found to be 89.80 and 89.77% respectively. The matured oocytes were picked up and denuded by treating them with 0.1% hyaluronidase and by repeated pipetting through a fine boar pipette. The denuded oocytes were transferred in fert- TALP medium (fertilization medium). The capacitated sperm having concentration of 1×106 live sperm/ml were used for in-vitro fertilization. Oocytes were co-incubated with spermatozoa for 18 h at 38.5±1°C in an atmosphere of 5% CO2 in a humidified air. Forty-eight hours post insemination the cleavage rates of 42.20 and 39.80% were obtained for prepubertal and pubertal goat oocytes respectively.